The Gender of Things How Epistemic and Technological Objects Become Gendered (Taylor & Francis, 2024)
Gender studies; feminist new materialism; gendered objects; history of science; material culture; technoscience
English
Keywords: Gender studies, gender groups; Gender studies; feminist new materialism; gendered objects; history of science;material culture; technoscience